Feasibility of Non-Invasive Vagus Nerve Stimulation (gammaCore VET™) for the Treatment of Refractory Seizure Activity in Dogs - Robinson, Kelsey; Platt, Simon; Stewart, Georgina; Reno, Lisa; Barber, Renee; Boozer, Lindsay (Frontiers in Veterinary Science, 2020)
Idiopathic epilepsy is the most common chronic neurologic condition in dogs. Approximately 20-30% of those dogs are refractory to standard medical therapy and commonly experience side effects from antiepileptic drugs. Non-invasive vagus nerve stimulation (nVNS) has been frequently used in human medicine as an adjunct seizure therapy with low incidence of adverse events. Canine studies are limited to invasive surgical implants with no non-invasive evaluations currently published. We investigated the feasibility and efficacy of nVNS (gammaCore VET) as an adjunct treatment for refractory epilepsy in dogs. In total, 14 client-owned dogs completed the trial of either 8- or 16-week treatment periods during which they received 90-120 second stimulation 3 times per day in the region of the left cervical vagus nerve. Owners recorded seizure type (focal or generalized) and frequency as well as any adverse effects. Out of 14 dogs, 9 achieved a reduction in seizure frequency and 4 were considered responders with a 50% or greater reduction in seizures from baseline to the final treatment period. However, there was no statistically significant difference in overall seizure frequency (p=0.53) or percent change in seizure frequency between groups (p=0.75). Adverse effects occurred in 25% of dogs originally enrolled, with reports of a hoarse bark and limb trembling, lethargy, behavioral changes, and an increase in seizure frequency. Non-invasive VNS was found to be safe and easy to administer with mild adverse events. It is considered a feasible treatment option as an adjunct therapy in refractory seizures and should be further investigated.